Improving the evidence base for delivery of public goods from public money in agri-environment schemes [version 2; peer review: 2 approved] - Helen Kendall; Gavin Stewart; Dianna Kopansky; Amy Taylor; Mark S. Reed; Guy Ziv; Pippa J. Chapman (Emerald Publishing, 2022)
There is growing interest around the world in more effectively linking public payments to the provision of public goods from agriculture. However, published evidence syntheses suggest mixed, weak or uncertain evidence for many agri-environment scheme options. To inform any future "public money for public goods" based policy, further synthesis work is needed to assess the evidence-base for the full range of interventions currently funded under agri-environment schemes. Further empirical research and trials should then focus on interventions for which there is mixed or limited evidence. Furthermore, to ensure the data collected is comparable and can be synthesised effectively, it is necessary to reach agreement on essential variables and methods that can be prioritised by those conducting research and monitoring. Future policy could then prioritise public money for the public goods that can most reliably be delivered, offering better value for taxpayers and improving the provision of ecosystem services from agricultural landscapes.